A wide-angle broadband absorber in graphene-based hyperbolic metamaterials. Issue 2 (15th October 2014) - Ning, Renxia; Liu, Shaobin; Zhang, Haifeng; Bian, Borui; Kong, Xiangkun
Abstract : A wide-angle broadband absorber which is realized by periodic structures containing graphene-based hyperbolic metamaterials (GHMM) and isotropic medium is theoretically investigated. The GHMM is composed of monolayer graphene and conventional dielectric, which the refractive index can be tuned by the chemical potential, the thickness of dielectric and phenomenological scattering rates, respectively. A periodic structure of GHMM can obtain a broadband absorption which is shown to absorb roughly 70% (relative bandwidth is larger than 45%) of all available electromagnetic wave in absorption bandwidth at normal incident angle. Compared with some previous designs, our proposed structure has a relative bandwidth over a broad frequency range in mid-infrared. This kind periodic structures offer additional opportunities to design novel optoelectronic devices.